2011
DOI: 10.2147/btt.s27343
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of infliximab in refractory Behçet’s disease-associated and idiopathic posterior segment uveitis: a prospective, follow-up study of 50 patients

Abstract: PurposeTo evaluate the long-term efficacy of infliximab in patients with refractory Behçet’s disease (BD)-associated and idiopathic posterior uveitis (PU).MethodsSingle center, prospective, 6-year duration, follow-up study on 50 consecutive patients (20 [40%] males and 30 [60%] females with a mean age of 37.5 ± 12.3 years) with refractory BD-associated PU (36 patients) and idiopathic PU (14 patients) who had failed at least one immunosuppressive drug. At baseline, patients received prednisone 1 mg/kg/day with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…In agreement with the literature, 96% of patients were complete or partial responders. An open-label study of 36 patients with BD and posterior refractory uveitis treated with IFX concluded that 91% of patients had complete or partial response after 37.3 months of follow-up [27]. A recent literature review regarding the use of anti-TNF agents in 369 BD patients, showed that 89% of patients with uveitis treated with IFX presented a sustained response [8].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the literature, 96% of patients were complete or partial responders. An open-label study of 36 patients with BD and posterior refractory uveitis treated with IFX concluded that 91% of patients had complete or partial response after 37.3 months of follow-up [27]. A recent literature review regarding the use of anti-TNF agents in 369 BD patients, showed that 89% of patients with uveitis treated with IFX presented a sustained response [8].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of TNF-α inhibitors is considered in BD patients who exhibit an inadequate response to topical and/or conventional systemic therapies, such as corticosteroids, CsA and colchicine, or those with refractory ocular involvement. Although there are no controlled trials, several open-label clinical trials and nonrandomized comparative studies have reported the efficacy of intravenous infliximab for BD-associated uveitis (17)(18)(19)(20)(21), among TNF-α inhibitors, only infliximab is approved for the treatment of BD-associated uveitis in Japan. However, little is known about the efficacy of infliximab in ESRD patients on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality level of evidence is warranted to assist the practicing rheumatologist in toward difficult-to-treat cases of BD. Table 4 shows a summary of studies that addressed the use of anti TNF-α agents in patients with BD [43]. -More patients remained free of nodular skin lesions (85% versus 25%).…”
Section: Behçet's Diseasementioning
confidence: 99%